The Image of Russia in South Africa Media Discourse: Frames and Metaphors - Olga A. Solopova; Natalia N. Koshkarova (RUDN Journal of Language Studies, Semiotics and Semantics)
Inter-BRICS cooperation is one of the priorities of Russian foreign policy. This indicates a need to understand perceptions of Russia’s image construal and mechanisms of its formation in BRICS’ media discourses. The study seeks to identify the peculiarities of Russia’s image construal in South African media discourse (2011-2024). The source of the material was the NOW corpus (News on the Web) that allowed for creating a virtual sub-corpus. The latter included 1000 articles in English, published in major South African newspapers. Corpus and computer linguistics techniques were used to get frequency lists, find N-grams, collocations and thematic clusters: the NOW corpus manager and the Conceptoscope software analytical complex. The frame, metaphorical modeling, cognitive and discourse methods were used to qualitatively analyze the data. The findings suggest that the image of Russia is framed indirectly in South African discourse: through other countries’ images and interstate relations. The diagnostic frame “partnership” and two prognostic subframes “progress” and “degradation” are dominant in structuring Russia’s image construal. The frame “partnership” is actualized by lexemes with the semantics of cooperation, jointness, and metaphors of “relationship”. The prognostic subframe “progress” is manifest in the use of lexemes with the semantics of expansion, increase, deepening, and “path” metaphors. The prognostic subframe “degradation” is textualized through metaphors with negative connotations. The findings have important implications for clarifying the criteria of frame identification, relying on corpus-based and computational tools, developing discourse theory by introducing the data of South African media discourse.